American Orthopaedic Foot and Ankle Society (AOFAS) Ankle-Hindfoot Score: a study protocol for the translation and validation of the Dutch language version - Cornelis H Van der Vlies; Esther M M van Lieshout; Michael H J Verhofstad; Duncan E Meuffels; A Siebe de Boer; Wim E Tuinebreijer; P Ted Den Hoed (BMJ Open)
Introduction The American Orthopaedic Foot and Ankle Society (AOFAS) Ankle-Hindfoot Score is among the most commonly used instruments for measuring the outcome of treatment in patients who sustained a complex ankle or hindfoot injury. It combines a clinician-reported and a patient-reported part. A valid Dutch version of this instrument is currently not available. Such a translated and validated instrument would allow objective comparison across hospitals or between patient groups, and with shown validity and reliability it may become a quality of care indicator in future. The main aims of this study are to translate and culturally adapt the AOFAS Ankle-Hindfoot Score questionnaire into Dutch according to international guidelines, and to evaluate the measurement properties of the AOFAS Ankle-Hindfoot Score-Dutch language version (DLV) in patients with a unilateral ankle or hindfoot fracture.Methods and analysis The design of the study will be a multicentre prospective observational study (case series) in patients who presented to the emergency department with a unilateral ankle or hindfoot fracture or (fracture) dislocation. A research physician or research assistant will complete the AOFAS Ankle-Hindfoot Score-DLV based on interview for the subjective part and a physical examination for the objective part. In addition, patients will be asked to complete the Foot Function Index (FFI) and the Short Form-36 (SF-36). Descriptive statistics (including floor and ceiling effects), internal consistency, construct validity, reproducibility (ie, test–retest reliability, agreement and smallest detectable change) and responsiveness will be assessed for the AOFAS DLV.Ethics and dissemination This study has been exempted by the Medical Research Ethics Committee (MREC) Erasmus MC (Rotterdam, the Netherlands). Each participant will provide written consent to participate and remain anonymised during the study. The results of the study are planned to be published in an international, peer-reviewed journal.Trial registration number NTR5613. pre-result.